PERANAN SOLIDARITAS ANGGOTA SANGGAR DALAM MEMBENTUK KAMPUNG SENI BUDAYA GEGESIK SEBAGAI PELESTARIAN BUDAYA LOKAL (Studi Deskriptif di Sanggar Hidayat Jati Kecamatan Gegesik, Kabupaten Cirebon) - Faishal Yazid Hibatullah, - (2021)
Gegesik arts and culture village, located in Gegesik District, Cirebon Regency, West Java Province, is one of the areas used for the preservation of local culture. Globalization has an impact on the development of local culture. Hidayat Jati Studio is one of the studios formed by the Ministry of Education and Culture of the Republic of Indonesia, which is expected to be able to answer the challenges of changing times in preserving local culture in Gegesik District. This study explains the role of solidarity carried out by members of the studio in forming the Gegesik cultural arts village as an effort to preserve Cirebon's local culture. The formulation of the problem in this study is (1) what is the general description of the solidarity of Hidayat Jati Sanggar members with other studio members in forming the Gegesik cultural arts village? (2) what are the factors behind the solidarity of Hidayat Jati Sanggar members with other studio members in forming the Gegesik cultural arts village? (3) how is the contribution of members of Sanggar Hidayat Jati to the formation of the Gegesik cultural arts village as a preservation of local Cirebon culture?. The theoretical study used is the perspective of Emile Durkheim's theory of solidarity and Putnam's theory of social capital. This study uses a mixed method (mixed method) and uses a sequential exploratory strategy. The results of this study indicate that (1) Solidarity among studio members is divided into mechanical solidarity and organic solidarity. (2) The factors that can form the Gegesik cultural arts village are internal factors and external factors. Internal factors, including the history and reasons for the establishment of the Gegesik cultural arts village and the role of members of the Hidayat Jati Studio. Then external factors, including social relations carried out by members of Sanggar Hidayat Jati and the emergence of globalization. (3) Based on the results of the questionnaire analysis that has been filled out by 100 respondents in Gegesik District, it shows that the contribution of members of Sanggar Hidayat Jati to the formation of the Gegesik cultural arts village is 48.3%. Contributions were made by members of Sanggar Hidayat Jati to the formation of the Gegesik cultural arts village as a preservation of local Cirebon culture, namely through programs that were carried out and achievements made by members so that the community could feel the benefits.